Modulation of sensitization processes in the management of pain and the importance of descending pathways: a role for tapentadol?. (2nd June 2020) - Caraci, Filippo; Coluzzi, Flaminia; Marinangeli, Franco; Mercadante, Sebastiano; Rinonapoli, Giuseppe; Romualdi, Patrizia; Nicora, Mariaflavia; Dickenson, Anthony H.
Abstract: Objective: This paper presents and discusses recent evidence on the pathophysiological mechanisms of pain. The role of tapentadol – an opioid characterized by an innovative mechanism of action (i.e. µ-opioid receptor [MOR] agonism and inhibition of noradrenaline [NA] reuptake [NRI]) – in the modulation of pain, and the most recent pharmacological evidence on this molecule (e.g. the µ-load concept) are also presented and commented upon. Methods: Narrative review. Results: Solid evidence has highlighted the importance of central sensitization in the transition from acute to chronic pain. In particular, the noradrenergic system holds a major role in limiting central sensitization and the progression to chronic pain. Therefore, pharmacological modulation of the noradrenergic system appears to be a well-grounded strategy for the control of chronic pain. Tapentadol is characterized by a to-date-unique mechanism of action, since it acts both as a MOR agonist and as an inhibitor of NA reuptake. The synergistic interaction of these two mechanisms allows a strong analgesic effect by acting on both ascending and descending pathways. Of note, the reduced µ-load of tapentadol limits the risk of opioid-related adverse events, such as gastrointestinal disturbances. Moreover, the NA component becomes predominant, at least, in some types of pain, with consequent specific clinical efficacy in the treatment of neuropathic and chronic pain. Conclusions: According to these characteristics, tapentadol appears suitable in the treatment of severe uncontrolled chronic pain characterized by both a nociceptive and a neuropathic component, such as osteoarthritis or back pain.